The results of study of collection cultivars and potato new breeding numbers according to agronomic traits - I. V. Lyskova; P. V. Permyakov; E. I. Kratyuk (Аграрная наука Евро-Северо-Востока, 2024)
The article presents the results of study of collection cultivars and new breeding numbers of potato for 2020–2023 in the agroecological conditions of the Kirov region according to the main agronomic traits. The early-ripening cultivar ‘Udacha’ (All-Russia Research Institute of Potato Farming), the mid-early cultivar ‘Nevsky’ (North-Western Research Institute ofAgriculture), and the mid-ripening cultivar ʻChaika’ (FANC North-East) were used as standards. In the group of early ripening cultivars, the ʻUtenok’ (Russia) had the most stable productivity indicator (CV = 32 %), in dry conditions of 2022 the cultivar exceeded the standard by 35 % (297 g/bush); among the foreign cultivars, the cultivar ʻDundrum’ (Great Britain) with an average productivity of 462±132 g/bush was selected (CV = 29 %). In the group of mid-early cultivars, in terms of productivity and stability of the indicator, the following cultivars were distinguished: ʻSkazka’ (Russia) – 423±120 g/bush (CV = 28 %), ʻLileya’ (Belarus) – 463±149 g/bush (CV = 32 %). In the group of mid-season cultivars, high productivity (467±260 g/bush (CV = 56 %)) was formed by the nematode-resistant ʻSanetta’ (Germany) and the cultivar ʻValkora’ (Bulgaria) – 523±220 g/bush (CV = 42 %). As a result of breeding work, the most promising selection numbers according to the productivity were identified: 69-21 – 702 g/bush, 283-21 – 685 g/bush; with early accumulation of yield – selection numbers 69-21, 285-21, 184-21 with productivity of 490, 390 and 350 g/bush, respectively. Based on the commercial quality of the tubers, the following were selected: 69-21 with large, even pink tubers, 19-21 with purple tubers. In the nursery of the preliminary test, based on the results of the assessment in 2023 the following were distinguished: by productivity 195-21 and 234-21; by early maturity 3-21, 199-21, 234-21; by resistance to common scab 202-21, 208-21, 199-21.